Unveiling the therapeutic role of Dachaihu decoction in acute cholecystitis: a comprehensive systematic review and meta-analysis of its efficacy and safety - Liu, Xin-xin; Ma, Ying-qi; Kong, Ling-yao; Su, You-zhu; Robinson, Nicola; Liu, Jian-ping (Frontiers in Pharmacology, 2024)
Background Dachaihu decoction (Da chaihu tang) plays a crucial role in treating acute illnesses. Recently, a significant number of clinical studies on Dachaihu decoction for AC have been published. This study was conducted to assess the efficacy and safety of Dachaihu decoction in patients with this condition. Methods To identify relevant RCTs, eight databases and three clinical trial registries were searched from inception to June 30, 2024.Two researchers independently screened and extracted data from eligible studies using Endnote X9 and Microsoft Office Excel 2019. The RoB 2.0 was employed to assess the risk of bias in the included studies. Stata 17.0 was used for data analysis. Publication bias and its impact on result stability were evaluated using a funnel plot and the "Trim and Fill" method. The quality of evidence was graded using the GRADE assessment system. Results Thirty-three RCTs involving 2851 participants were included. The treatment group has demonstrated improved clinical efficacy (RR = 1.18, 95% CI 1.13 to 1.24) , significantly reduced length of hospital stay (MD = -1.78 days, 95% CI -2.02 to -1.53) and the incidence of adverse events (RR = 0.31, 95% CI 0.20 to 0.48). Additionally, there appeared to be reductions in the time for abdominal pain to resolve (MD = -1.92 days, 95% CI -2.33 to -1.51), fever to disappear (MD = -1.52 days, 95% CI -1.90 to -1.14, white blood cell counts to return to normal (MD = -2.89 days, 95% CI -3.32 to -2.46), ALT levels (MD = -11.88 U/L, 95% CI -15.29 to -8.47), AST levels (MD = -8.74 U/L, 95% CI -9.76 to -7.72), neutrophil percentage (MD = -9.68, 95% CI -11.33 to -8.03), TNF-α levels (SMD=-2.10 pg/L, 95% CI -2.43 to -2.78). Certainty of evidence (moderate to low certainty). Conclusions Dachaihu decoction may be an effective botanical formula for managing AC, and a lower incidence of adverse events. However, due to the substantial risk of bias and heterogeneity across the included studies, these findings should be interpreted with caution and require further validation through well-designed, high-quality trials.